Rolling shear properties of cross-laminated timber (CLT) made from Australian Radiata Pine – An experimental study. (October 2021) - Li, Xin; Ashraf, Mahmud; Subhani, Mahbube; Kremer, Paul; Li, Haitao; Anwar-Us-Saadat, Mohammad
Abstract: Cross-laminated timber (CLT) is produced from renewable bio-composite material and has been gaining popularity in building industry largely due to easily customised panellised construction technique, which is fast, efficient, minimises construction risk and waste. CLT is often considered as a sustainable alternative to traditional construction materials, and can be used to complement steel and concrete to build a sustainable future. CLT is reported to provide excellent resistance against both out-of-plane and in-plane loading but rolling shear properties have been recognized as one of the critical parameters that often controls the design resistance when CLTs are subjected to out-of-plane loading scenario. Rolling shear characteristics are highly dependent on wood species, sawing patterns and width-to-thickness ratio ( wl / tl ) of a single lamella. This paper presents a thorough investigation on rolling shear properties of two types three-layer CLT panels (CL3/105 and CL3/135) produced by XLam from Australian Radiata Pine. Rolling shear properties were measured using two test methods i.e. short-span four-point bending test and planar shear test. Typical rolling shear failures were observed in samples tested using short-span bending method and rolling shear stresses were evaluated by using various analytical methods. Planar shear samples also failed in rolling shear, as expected, and showed comparable results. Existing theoretical approaches were used to evaluate the rolling shear properties with a characteristic rolling shear strength of 2.0 MPa and shear modulus of 65.5 MPa for the considered Radiata Pine CLT panels. In addition, an empirical equation has been proposed based on the rolling shear results for other similar species published in literature and the current observations were compared against the proposed equation.